A morte em forma de poesia: comoção, indignação e reivindicação em cordéis midiatizados - Simone Mendes (Estudos de Literatura Brasileira Contemporânea)
his article makes a reflection departing from the analyzes that are being developed in my doctoral research, whose focus builds itself departing from the existence of an argumentative dimension in cordel literature, that makean interface with the information media. In a rhetorical argumentation, logical thought and demonstration aren’t enough to guarantee the efficiency of the interaction, because, while basing itself on the interlocutor adhesion to a thesis, through belief, other re-requirements are raised and need to be observed, like the speaker ethos or his honesty, sincerity, sense of justice, seriousness and reliability; the pathos or the ability of raising emotions in the public logos or the discourse itself and its rationality, using by the speaker to reinforce his point of view and his socio-discursive representations around the given theme. When we analyze cordel works whose theme is homicide, we could find this theoretical- methodological reasoning.